Diagnostic value of the microcolon using ultrasonography in small bowel atresia - Hao Ju; Shu Feng; Ying Huang (BMC Pediatrics, 2022)
Abstract Background Microcolon helps diagnose small bowel atresia (SBA) using contrast enema. However, there are no ultrasonography (US) microcolon criteria for diagnosing SBA. Therefore, this study aimed to evaluate colon accuracy and other characteristics for diagnosing SBA by US, using surgical or clinical information as the reference standard. Methods US was performed on 46 neonates aged ≤ 7 days old. In the study group (n = 15), neonates with SBA were confirmed following surgery. In the study group without SBA (n = 15), neonates with other gastrointestinal problems besides SBA were confirmed by surgical or clinical follow-up. Sixteen neonates without gastrointestinal problems were classified as the control group. The colonic diameter was measured, and colonic gas was sought and observed. Statistical analysis was performed to compare US parameters between the study group and other two groups. The optimal cut-off value of the colonic diameter for SBA diagnosis was obtained using receiver operating characteristic analysis. Results Colonic diameters (0.5 cm) in the study group (interquartile ranges [IQR], 0.5–0.6 cm) was significantly smaller than that in the group without SBA (0.9 cm; IQR, 0.8–1.2 cm) (P <  0.001) and in the control group (1.2 cm; IQR, 0.8–1.35 cm) (P < 0.001). Optimum cut-off value for diagnosing SBA was 0.65 cm (sensitivity, 90.3%; specificity, 86.7%; accuracy, 89.1%) for the colonic diameter. Combining microcolon and gas-negativity showed the best performance in SBA diagnosis using US, with increased accuracy (91.3%). Conclusion A colon < 0.65 cm in diameter should be called a microcolon; combining US with gas-negativity is an essential diagnostic basis for SBA.